sebuah HUBUNGAN DUKUNGAN KELUARGA DENGAN KEKAMBUHAN SKIZOFRENIA DI INDONESIA: TINJAUAN SISTEMATIS - Ulil Albab Habibah; Satria Akbar Putra Asmara; Triyana Indah Purwati; Rina Hilmina (Jurnal Riset Kesehatan, 2026)
Schizophrenia is a chronic mental disorder characterized by disturbances in perception, emotion, and thought processes, affecting approximately 24 million people worldwide. In Indonesia, more than 400,000 individuals are estimated to live with schizophrenia. Relapse remains a major challenge in disease management and is influenced by various psychosocial factors, including family support. A systematic review was conducted in December 2025 using PubMed, ScienceDirect, and Google Scholar to identify relevant studies published between 2021 and 2025. Study selection followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The risk of bias was assessed using the Joanna Briggs Institute (JBI) Critical Appraisal Tools. Sixteen cross-sectional studies involving a total of 1,093 participants met the inclusion criteria. The included studies demonstrated low to high risk of bias. Most studies reported a statistically significant association between family support and relapse prevention or medication adherence among patients with schizophrenia (p < 0.05). Family support plays a crucial role in reducing relapse among patients with schizophrenia in Indonesia. Family-based interventions should be strengthened as part of long-term treatment strategies to improve clinical outcomes.